Relationship between drug interactions and drug-related negative clinical outcomes in two community pharmacies - Gonzalo M; Arrebola I; Cremades J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
Drug interactions may represent an iatrogenic risk that should be controlled in community pharmacies at the dispensing level. Aim: We analyzed the association between potential drug-drug interactions (DDIs) and negative clinical outcomes.Methods: We used dispensing data from two community pharmacies: instances where drug dispensing was associated with a potential DDI and a comparison group of randomized dispensing operations with no potential DDI. In cases where potential DDIs were detected, we analyzed the underlying negative clinical outcomes. Age and gender data were included in the analysis.Results: During the study period, we registered 417 potential DDIs. The proportion of women and age were higher in the study group than in the comparison group. The average potential DDIs per patient was 1.31 (SD=0.72). The Consejo General de Colegios Oficiales de Farmacéuticos (CGCOF) database did not produce an alert in 2.4% of the cases. Over-the-counter medication use was observed in 5% of the potential DDI cases. The drugs most frequently involved in potential DDIs were acenocoumarol, calcium salts, hydrochlorothiazide, and alendronic acid, whereas the most predominant potential DDIs were calcium salts and bisphosphonates, oral antidiabetics and thiazide diuretics, antidiabetics and glucose, and oral anticoagulant and paracetamol. The existence of a drug-related negative clinical outcome was observed only in 0.96% of the potential DDI cases (50% safety cases and 50% effectiveness cases). Conclusions: Only a small proportion of the detected potential DDIs lead to medication negative outcomes. Considering the drug-related negative clinical outcomes encountered, tighter control would be recommended in potential DDIs with NSAIDs or benzodiazepines.